Tax policy practices as a part of fiscal policy in Turkey - ZÜLFÜOĞLU, ÖZKAN (My University, 2022)
After the 2008 global crisis, the role of fiscal policy in ensuring economic stability has once again become an important topic of discussion. As of 2022, there has been a significant increase in inflation in the world. In addition, it is often predicted that the world economy will enter a recession again. In such a case, the issue of how the tax policy will be implemented becomes important. In this study, tax policy practices, which are a component of fiscal policy, will be discussed in a historical perspective in Türkiye. Then, the relationship between tax revenue and inflation will be examined econometrically. Findings show that tax policy in Türkiye tends towards the goal of generating income rather than being used as a fiscal policy tool.
Keywords: Fiscal policy; Taxes; Inflation